RELASI SOSIO-EKONOMI PETANI DENGAN PEMILIK LAHAN MELALUI KONSEP MUKHĀBARAH DAN MUZĀRA‘AH DI DESA ARANG LIMBUNG KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Rasiam Rasiam (Fakultas Syariah (Syari'ah Faculty ), 2016)
This writing addresses the practice of mukhabarah and muzara’ah in cultivating farms in Arang Limbung village, Sungai Raya district, Kubu Raya regency. Socioeconomic cooperation between farmhands and land lords constitute a mutual symbiosis; by cooperating they can handle the problems of cultivating farms. Landlords do not have sufficient time and skill to cultivate their farms while farmhands do not have land to plough. Consequently, they must collaborate through the concept of mukhabarah and muzaraah in which the profit sharing is according to the common agreement. This socioeconomic cooperation is based on trust and fair profit sharing that include: first, the basis of this cooperation is to help each other instead of doing business; and second, the profit sharing is according to farms production. Thus, this collaboration is not only based on profit objectives but social consideration as well. Keywords: Mukhābarah, muzāra‘ah, socio economic cooperation.